Guarded dual authentication based DRM with resurgence dynamic encryption techniques - Agarwal, Neha; Rana, Ajay; Pandey, J.P. (Enterprise information systems, 2019)
Cloud computing is the emergent technology that face one of the significant issues time with data security while outsourcing the data onto the cloud in recent. Some cryptographic techniques have been used for protection in form of identity, attributes and prediction algorithms nonetheless these algorithms lack their performance and becomes are very prone to attackers when an unauthorized user reunited the system with dissimilar way for privileges to the similar data files. The essential need of this data security solved by some enhanced cryptographic techniques in DRM utilizing a secure privacy preserving data sharing with encryption techniques of Dynamic Unidirectional Proxy Re-Encryption. This technique is based on Cipher text Policy Attribute by providing the privacy, integrity and security of the data while retrieving.